Making Patients Fit for Surgery: Introducing a Four Pillar Multimodal Prehabilitation Program in Colorectal Cancer. (October 2019) - van Rooijen, Stefanus J.; Molenaar, Charlotte J.L.; Schep, Goof; van Lieshout, Rianne H.M.A.; Beijer, Sandra; Dubbers, Rosalie; Rademakers, Nicky; Papen-Botterhuis, Nicole E.; van Kempen, Suzanne; Carli, Francesco; Roumen, Rudi M.H.; Slooter, Gerrit D.
Abstract : Background: Considering the relation between preoperative functional capacity and postoperative complications, enhancing patients' functional capacity before surgery with a prehabilitation program may facilitate faster recovery and improve quality of life. However, time before surgery is short, mandating a multimodal and high-intensity training approach. This study investigated feasibility and safety of a prehabilitation program for colorectal cancer. Methods: Multimodal prehabilitation was offered to patients eligible for participation and they were assigned to an intervention or control group by program availability. The prehabilitation program consisted of the following four interventions: in-hospital high-intensity endurance and strength training, high-protein nutrition and supplements, smoking cessation, and psychological support. Program attendance, patient satisfaction, adverse events, and functional capacity were determined. Results: Fifty patients participated in this study (prehabilitation 20, control 30). Program evaluation revealed a high (90%) attendance rate and high level of patient satisfaction. No adverse events occurred. Endurance and/or strength were improved. Eighty-six percent of patients with prehabilitation recovered to their baseline functional capacity 4 weeks postoperatively, 40% in the control group ( P < 0.01). Conclusions: Multimodal prehabilitation including high-intensity training for colorectal cancer patients is feasible, safe, and effective. A randomized controlled trial (NTR5947) was initiated to determine whether prehabilitation may lower morbidity and mortality rates in colorectal surgery.